How are AI assistants changing higher education? - Schön, Eva-Maria; Neumann, Michael; Hofmann-Stölting, Christina; Baeza-Yates, Ricardo; Rauschenberger, Maria (Frontiers in Computer Science, 2023)
Context Higher education is changing at an accelerating pace due to the widespread use of digital teaching and emerging technologies. In particular, AI assistants such as ChatGPT pose significant challenges for higher education institutions because they bring change to several areas, such as learning assessments or learning experiences. Objective Our objective is to discuss the impact of AI assistants in the context of higher education, outline possible changes to the context, and present recommendations for adapting to change. Method We review related work and develop a conceptual structure that visualizes the role of AI assistants in higher education. Results The conceptual structure distinguishes between humans, learning, organization, and disruptor, which guides our discussion regarding the implications of AI assistant usage in higher education. The discussion is based on evidence from related literature. Conclusion AI assistants will change the context of higher education in a disruptive manner, and the tipping point for this transformation has already been reached. It is in our hands to shape this transformation.